ENHANCING SEISMIC SAFETY THROUGH THE APPLICATION OF ADVANCED PARAMETRIC DESIGN SOLUTIONS - S.M.Mirzababayeva; Z.A.Abobakirova (Western European Studies, 2025)
This article analyzes the modern challenges of the sustainable architecture concept, the possibilities of addressing them through the parametric design approach, and the ways to enhance the seismic stability of buildings. The study explores the impact of parametric design technologies on environmental, social, and technical efficiency, as well as the prospects for applying this approach in the seismically active regions of Uzbekistan. In the course of the research, the scientific works of several scholars working in this field were studied
Keywords: sustainable architecture; parametric design; seismic stability